Managing changes, transforming the sector: the case of the Colombian Roundtable for Sustainable Cattle - Triana Ángel, Natalia; Burkart, Stefan (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The global and Latin American cattle sectors have considerable potential for large-scale food production, thus positioning themselves as a fundamental axis for global food security. Cattle production is, however, simultaneously responsible for at least 9.5% of the global greenhouse gas emissions, finding itself increasingly at the mercy of a variety of factors, such as climate change and an increasing demand, forcing it to transform its forms of production (Gerber et al., 2013).